2019
DOI: 10.3389/fpls.2019.01355
|View full text |Cite
|
Sign up to set email alerts
|

In-Field Detection and Quantification of Septoria Tritici Blotch in Diverse Wheat Germplasm Using Spectral–Temporal Features

Abstract: Hyperspectral remote sensing holds the potential to detect and quantify crop diseases in a rapid and non-invasive manner. Such tools could greatly benefit resistance breeding, but their adoption is hampered by i) a lack of specificity to disease-related effects and ii) insufficient robustness to variation in reflectance caused by genotypic diversity and varying environmental conditions, which are fundamental elements of resistance breeding. We hypothesized that relying exclusively on temporal changes in canopy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 76 publications
0
30
0
Order By: Relevance
“…For example, a SVI has been previously proposed to measure yellow rust in mid-late stage wheat [ 10 ] which relies on spectral data obtained at 860 nm, which is outside of the spectral range at which the spectroradiometer used in this study operates. Further improvement could come in form of replacing or combining the visual scores, used as ground truth data in this study, with more objective digital methods to estimate disease infection, such as destructive sampling and image analysis of diseased leaves, as was done in a similar study of field-based prediction of STB [ 13 ]. In that study, the authors reported a prediction accuracy of r = 0.53 when validating their proposed model in an independent test set.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a SVI has been previously proposed to measure yellow rust in mid-late stage wheat [ 10 ] which relies on spectral data obtained at 860 nm, which is outside of the spectral range at which the spectroradiometer used in this study operates. Further improvement could come in form of replacing or combining the visual scores, used as ground truth data in this study, with more objective digital methods to estimate disease infection, such as destructive sampling and image analysis of diseased leaves, as was done in a similar study of field-based prediction of STB [ 13 ]. In that study, the authors reported a prediction accuracy of r = 0.53 when validating their proposed model in an independent test set.…”
Section: Discussionmentioning
confidence: 99%
“…Following the correlation analysis, the data at each timepoint was split into an 80/20 training and test data set, where the training data was used to perform recursive feature elimination and the test set was reserved for the validation of the final model trained based on the results of the feature elimination. Thus, a minimal set of predictors was established by performing supervised feature selection by recursive feature elimination with random forest (RF) regression, by adapting a protocol and associated code by [ 13 ]. The feature elimination was performed separately for each time point and proceeded by stepwise elimination of predictors from 119 predictors down to one, repeated 30 times.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last two decades, genomics has revolutionized plant breeding mainly due to a reduction in genotyping costs, which results in the adoption of new technologies, such as linkage mapping, genome-wide association studies, genome-wide selection, and rapid generation advance [189]. Accurate genetic mapping and genome-wide selection require precise phenotyping of the plants.…”
Section: Cereal Phenomicsmentioning
confidence: 99%
“…Current reflectance-based crop disease models are not sufficiently robust to account for these environmental variations. This problem has been reviewed in Anderegg et al 24 and examined in detail in previous literature. 25,26…”
Section: Model Specificity Limitationsmentioning
confidence: 99%